Eye care for children with learning disabilities 2: Assessment of vision and visual needs. Issue 8 (August 2020) - Rughani, Sonal; Donaldson, Lisa
Abstract : In the second in our series discussing the vision of children with learning disabilities, Sonal Rughani and Lisa Donaldson offer practical advice and strategies on how to successfully engage children with learning disabilities to assess their eye health and vision needs (C76171, one distance learning CET point suitable for optometrists and dispensing opticians)